INTERNALISASI NILAI PENDIDIKAN AKHLAK MELALUI KEGIATAN KEPRAMUKAAN - Muhamad Slamet Yahya; Wakhidin Shodiq; Khafifatul Fian (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The many actions of a child with the fading of morals in daily life. Thus, this essay seeks to examine how to internalize the value of moral education at SMA Negeri 3 Purwokerto. This study employs a qualitative methodology, gathering data via interview techniques. After the data is collected, the author then reduces, analyzes, and ends with conclusions. The findings of this study demonstrate that fostering moral education has an important role, including as an effort to create a harmonious environment, to prevent a person from dissolving in luxury and pleasure, to create character, morals, and ethics by Islamic teachings, and as an effort to form a better person. The internalization of moral education at SMA Negeri 3 Purwokerto is seen from scouting activities with the execution of several initiatives, such as regular Friday training and social service, outbound, and “anjangsana”. The program is carried out to integrate the importance of Islamic education for moral development so that it can be inherent in each student.